Eksplorasi Plasma Nutfah Aren (Arenga pinnata Merr) di Kutai Timur, Provinsi Kalimantan Timur - ELSJE T. TENDA; ISMAIL MASKROMO; BAMBANG HELIYANTO (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Exploration of Sugar Palm (Arenga pinnata Merr) Germplasm in East Kutai, East Kalimantan Province To broaden the genetic base of the plant, in December 2009 a mission to acquire new germplasm of sugar palm was sent to East Kutai District, East Kalimantan Province. The target location was the village of Teluk Pandan, Kandolo sub-District and village of Peridan, Sangkuliran sub-District. Mission successfully identified two types of sugar palm; dwarf type from the Teluk Pandan village, Kandolo sub-District and Tall type from Paridan village, Sangkuliran sub-District. Dwarf type is observed to have high variability in term of stem height, stem length, male inflorescence, length of male peduncle, number of males inflorescence, number of female inflorescence and time period of sap production per bunch. While Tall type has high variability in term of stem height, length of male inflorescence, the number of male inflorescence, female inflorescence, stem length, number of female inflorescence, production of sap, and period of sap producing.